2014
DOI: 10.5897/ajb09.645
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent prevalence of Loa loa amicrofilaremia and microfilaremia status as defined by two markers: microfilaria and specific IgG4

Abstract: Loiasis infection is characterised by long term stability in infection status. The bases of such stability are not well known. As preliminary step toward verification of possible genetic involvement in this stability, a survey in a homogeneous population (n = 106) of a village from an endemic zone of Gabon was undertaken. The distribution of Loa loa microfilaremia according to age revealed a significant relationship between age and the presence of microfilariae in the blood (p = 0.0059). The proportion of micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Overall, 76.9% in the under 15-year-old age group were positive and serological negativity was rare. Both findings are in line with previous reports [20][21][22]. Interestingly, comparison of different loiasis sub-groups showed lower median AU in the microfilaremic population than in patients with occult loiasis.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 93%
See 3 more Smart Citations
“…Overall, 76.9% in the under 15-year-old age group were positive and serological negativity was rare. Both findings are in line with previous reports [20][21][22]. Interestingly, comparison of different loiasis sub-groups showed lower median AU in the microfilaremic population than in patients with occult loiasis.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 93%
“…microfilaremic or occult loiasis, has repeatedly been described [ 19 , 20 ]. Further, it was found that Loa-specific IgG4 positivity can reach up to 100% in individuals living in high transmission areas [ 21 ]. Here, only total IgG was analyzed rather than specific subclasses, but still differences between loiasis subgroups were found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2014;13(4):593-597. 97 Third, serum from amicrofilaremic individuals can kill microfilariae via a mechanism involving antibodies and eosinophils cells. 56 Fourth, several molecules seem to be the preferential target of amicrofilaremic antibodies but not antibodies from microfilaremic individuals.…”
Section: Outlook: Concomitant Immunity As Key In the Development Of A...mentioning
confidence: 99%